2006
DOI: 10.1038/nature05010
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells are essential intermediaries in regulatory T-cell tolerance

Abstract: Contrary to the proinflammatory role of mast cells in allergic disorders, the results obtained in this study establish that mast cells are essential in CD4+CD25+Foxp3+ regulatory T (T(Reg))-cell-dependent peripheral tolerance. Here we confirm that tolerant allografts, which are sustained owing to the immunosuppressive effects of T(Reg) cells, acquire a unique genetic signature dominated by the expression of mast-cell-gene products. We also show that mast cells are crucial for allograft tolerance, through the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
621
3
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 675 publications
(661 citation statements)
references
References 30 publications
29
621
3
8
Order By: Relevance
“…40 However, the role gzmB may play in any of these processes is unknown. Recent evidence implicates mast cell-derived gzmB in the inhibition of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…40 However, the role gzmB may play in any of these processes is unknown. Recent evidence implicates mast cell-derived gzmB in the inhibition of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells also contribute to two additional models of immunosuppression 82,83 . Depinay et al 82 reported that the bites of Anopheles mosquitoes can impair the development of antigenspecific T-cell responses in a model of DTH to ovalbumin in mice, but only if mast cells are present in the bitten skin.…”
Section: Negative Immunomodulatory Functions In Vivomentioning
confidence: 99%
“…Depinay et al 82 reported that the bites of Anopheles mosquitoes can impair the development of antigenspecific T-cell responses in a model of DTH to ovalbumin in mice, but only if mast cells are present in the bitten skin. Lu et al 83 showed that mast cells were essential for the optimal induction of tolerance to skin allografts, which requires the participation of CD4 + CD25 + FOXP3 + regulatory T cells. Regulatory T cells are a source of IL-9, and IL-9 can mediate the suppression of alloreactive CD8 + T cells and act as a mast-cell survival and/or growth factor (reviewed in Ref.…”
Section: Negative Immunomodulatory Functions In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Mast cell mediators cause vasopermeability and oedema (Binstadt et al, 2006) and are important recruiters of leukocytes. Moreover, mast cells are essential in the induction of regulatory T-cell tolerance (Lu et al, 2006). Long implicated in human inflammatory arthritis (Woolley, 2003), recent evidence in mice has highlighted a pivotal role of mast cells in the initiation of inflammatory arthritis initiated by immune complex formation (reviewed, (Nigrovic and Lee, 2005)).…”
Section: The Key Playersmentioning
confidence: 99%